Mouse CD52 is predominantly expressed in the cauda epididymis, regulated by androgen and lumicrine factors - Dwi Ari Pujianto; Silvani Permatasari (Wolters Kluwer Medknow Publications, 2021)
Background: Sperm maturation takes place through contact between sperm and proteins produced in the epididymal lumen. CD52 had been characterised in the sperm; however, the expression and its regulation in the epididymis are mostly unknown. Aim: This study aimed to analyse the expression and regulation of CD52 in the mouse epididymis. Setting and Design: Experimental design was used in this study. Materials and Methods: Epididymis tissues from mice strain Deutch Democratic Yokohama were used as sources of total RNA. Bioinformatic tool was used to predict signal peptides. Quantitative real-time reverse transcription-polymerase chain reaction was used to analyse tissue distribution, androgen, testicular factors dependency and postnatal development. Statistical Analysis: One-way analysis of variance was used to analyse differences between treatment and control untreated group. P < 0.05 was determined as a significant difference. Results: CD52 amino acid sequence contains a signal peptide, indicating it is a secretory protein. CD52 exhibited region-specific expression in the epididymis, with the highest level being in the cauda. CD52 expression was regulated by androgen indicated by a significant downregulation at day 1 and day 3 following a castration (P < 0.05). Dependency on androgen was confirmed by injection of exogenous testosterone which prevented downregulation by 50%. Moreover, lumicrine factors also influenced CD52 expression indicated by ligation of efferent duct which also reduced expression at day 1 to day 5 following the ligation (P < 0.05). CD52 expression was developmentally regulated. This was shown by increase in the level of expression starting at day 15 postnatally. Conclusion: CD52 shows characteristics of genes involved in sperm maturation in the epididymis.